Observation of Source Plasma and Field Variations of a Substorm Brightening Aurora at L ∼ 6 by a Ground‐Based Camera and the Arase Satellite on 12 October 2017. Issue 11 (31st October 2022) - Chen, L.; Shiokawa, K.; Miyoshi, Y.; Oyama, S.; Jun, C.‐W.; Ogawa, Y.; Hosokawa, K.; Inaba, Y.; Kazama, Y.; Wang, S. Y.; Tam, S. W. Y.; Chang, T. F.; et al.
Abstract: Auroral brightening is one of the most common phenomena that occur during substorm onset and is usually recognized as a projection of the substorm‐associated magnetospheric plasma dynamics to the ionosphere. However, electromagnetic fields and plasma features associated with the substorm brightening arc have not been well understood. In this study, we present a comprehensive observation of the source plasma and field variations of a substorm brightening aurora in the inner magnetosphere. We performed a unique conjugate observation of a substorm brightening auroral arc observed by a ground‐based camera and by the Arase satellite in the magnetospheric source region at L ∼ 6. The event was observed at Tromsø (69.6°N, 19.2°E), Norway, on 12 October 2017. The brightening arc indicates east‐west structures with longitudinal scales of ∼0.5°–2.0°. Field‐aligned bi‐directional electrons with an energy range between 66 and 1, 800 eV were detected by the satellite, simultaneously with the appearance of the brightening arc in the camera. These electrons were probably supplied from the auroral brightening region in the ionosphere, indicating that the satellite was on the same field line of the brightening aurora. The magnetic and electric field data show characteristic fluctuations and earthward Poynting flux around the time that the satellite crossed the aurora. Anti‐phase oscillations between the thermal pressure and the magnetic pressure are also reported. Based on these observations, we suggest the possibility that a ballooning instability occurred in the source region of the substorm brightening arc in the inner magnetosphere at L ∼ 6. Plain Language Summary: A frequently occurring source of variations in the magnetosphere is the substorm, a process that causes energy dissipation into the atmosphere. Substorm is presented as the development of aurorae at high latitudes in the ionosphere. The study of substorm processes helps in understanding the near‐Earth space environment and the space weather. Along Earth's magnetic field lines, the aurora at a latitude of ∼65°N can be traced to ∼4–7 Earth radii away from the Earth at the equatorial plane in space. Using a ground‐based auroral camera, we can construct the correspondence between auroral motion and field and plasma variation at the satellite. This study reports such a unique event of substorm brightening arc observed at Tromsø, Norway, on 12 October 2017. Satellite observed bi‐directional electrons prove the connection between aurora break‐up at ∼100 km altitude and its source region in the magnetosphere at ∼30, 000 km away from Earth. Based on the magnetic wave spectrograms, auroral bead‐like structures and other observational results, we suggest the possibility that a ballooning plasma instability occurred in the source region of the substorm brightening arc in the inner magnetosphere. Key Points: Observation of plasma and field features in the source region of a sudden brightening auroral arc during a minor substorm onset at L ∼ 6 Energization of particles, field‐aligned electrons, and electromagnetic field fluctuations were observed during the arc crossing by Arase Several observational facts indicate the possibility of ballooning instability occurring at this substorm onset